Early surgery vs conservative management among asymptomatic aortic stenosis: A systematic review and meta-analysis. (December 2022) - Jaiswal, Vikash; Khan, Nida; Jaiswal, Akash; Dagar, Mehak; Joshi, Amey; Huang, Helen; Naz, Hira; Attia, Abdelrahman M.; Ghanim, Mohammed; Baburaj, Abiram; Song, David
Highlights: Aortic valve replacement remains the definitive choice of treatment for AS. All-cause mortality and adverse events are lower with early surgical valve repair. In high-risk AS patients, early surgery is safer than conservative management. Early intervention is crucial to prevent irreversible damage of AS. Abstract: Introduction: Although aortic valve replacement in severe symptomatic Aortic Stenosis (AS) are clearly outlined, the role of surgical intervention in asymptomatic severe AS remains unclear with limited evidence. The aim of our meta-analysis is to evaluate the efficacy and safety of early surgical aortic valve repair compared to conservative management. Methods: A systematic literature search was performed in PubMed, Scopus, Embase and Cochrane databases for studies comparing the early surgery versus conservative management among asymptomatic aortic stenosis patients. Unadjusted odds ratios (OR) were pooled using a random-effect model, and a p-value of < 0.05 was considered statistically significant. Results: A total of 5 articles (3 observational studies and 2 randomized controlled trials) were included. At a median followup of 4.1 years, here were significantly lower odds of all-cause mortality [OR = 0.30 (95 %CI:0.17–0.53), p < 0.0001], cardiovascular mortality [OR = 0.35 (95 %CI:(0.17–0.72), p = 0.005], and sudden cardiac death (OR = 0.36 (95 %CI: 0.15–0.89), p = 0.03) among early surgery group compared with conservative care. There was no significant difference between incidence of major bleeding, clinical thromboembolic events, hospitalization due to heart failure, stroke and myocardial infarction between the conservative care groups and early surgery. Conclusion: Among asymptomatic patients with AS, early surgery shows better outcomes in reducing all-cause mortality and cardiovascular mortality compared with conservative management approaches.